Oxidation of PAHs in water solutions by ultraviolet radiation combined with hydrogen peroxide - Stanislaw Ledakowicz; Jacek S. Miller; Dorota Olejnik (International Journal of Photoenergy)
The destruction of three polycyclic aromatic hydrocarbons (PAHs): benzo[a]pyrene, chrysene and fluorene in aqueous solution using advanced oxidation process H2O2/UV was investigated. The influence of pH, initial hydrogen peroxide and radical scavenger concentrations on the reaction rate was studied. The oxidation reactions most rapidly run in neutral and acidic solution at optimal hydrogen peroxide concentration (ca. 0.01 M). The degradation of benzo[a]pyrene and chrysene follows radical reaction, for fluorene the mechanism is not clear. The rate constants of the hydroxyl radicals and selected PAHs reaction were found to be 2.53×1010, 9.82×109 and 2.77×109M−1S−1 for benzo[a]pyrene, chrysene and fluorene, respectively